Performance and carcass characteristics of Sudan Desert sheep and goats on high roughage diets with added fat - El-Hag, M.G.; Kurdi, O.I.; Mahgoub, S.O. (Elsevier, 1985)
The effect of adding 10% tallow to a high roughage basal diet (75%) on animal performance and carcass characteristics of Sudan desert sheep and goats was investi- gated. Ten goats and 10 sheep were used in a 2 x 2 factorial design, with five animals per treatment. The animals were 1-1.5 years of age and 20-23 kg in weight. The experiment lasted 90 days. Addition of fat significantly decreased dry matter (DM) intake, more so in sheep (32%) than in goats (13%). There was also a significant difference between species in the DM intake with a higher intake for sheep. The interaction (diet X species) was also significant. However, both live-weight gain in goats and feed efficiency in sheep were improved by the inclusion of fat in the diet. Fat significantly increased diet TDN content in both species, but there was also a significant difference between species. The interaction (diet X species) was also significant. However, fat tended to depress N retention, particularly for goats. Digestibility of DM, OM, CF and NFE was depressed by fat inclusion in sheep and improved in goats. However, fat significantly improved EE digestibility for both species. The interaction (diet X species) was significant for digestion of DM, OM, CF and NFE. With or without fat in their diet, goats were superior in digesting DM, OM, CR, EE and NFE. Fat had no effect on dressinig percentage or other carcass characteristics. In general, responses of sheep and goats to fat inclusion were apparently different.